Women's autonomy in refusing risky sex and associated factors in Ethiopia: evidence from 2011 to 2016 EDHS data - Melkamu Dires Asabu (BMC, 2021)
Abstract Background Risky sexual behavior is a major public health concern of Ethiopians. Although studying the autonomy of women in refusing risky sex is significant to take proper actions, the issue is not yet studied. Accordingly, this population-based nationwide study was aimed at assessing women's autonomy in refusing risky sex and its associated factors in Ethiopia. Method The sample was limited to married women of 2011 (n = 8369) and 2016 (n = 8403) Ethiopian Demographic and Health Survey data. Women's autonomy in refusing risky sex was measured based on wives' response to 'not having sex because husbands have other women. To examine associated factors, socio-demographic variables were computed using binary logistic regression. Result The finding revealed that the trend of women's autonomy in refusing risky sex had declined from 78.9% in 2011 to 69.5% in 2016. Women aged from 25 to 34 were less likely autonomous in refusing sex compared to those who aged less than 24 years old (AOR = .7064; 95% CI 0.605, 0.965). The autonomy of women with higher educational status was three times more likely higher than those who have no formal education (AOR = 3.221; 95% CI 1.647, 6.300 respectively. The autonomy of women who are from rich households was more likely higher in comparison to women from poor households (AOR = 1.523; 95% CI 1.28, 1.813). The autonomy of women those who live in Tigray 2.9 times (AOR = 2.938; 95% CI 2.025, 4.263), Amhara 4.8 times (AOR = 4.870; 95% CI 3.388, 7.000), SNNP 1.9 times (AOR = 1.900; 95% CI 1.355, 2.664), and Addis Ababa 3.8 times (AOR = 3.809; 95% CI 2.227, 6.516) more likely higher than those who reside in Dire Dawa. Conclusion The autonomy of women in refusing risky sex has declined from 2011 to 2016. This infers that currently, women are more victimized than previously. Hence, possible interventions like empowering women shall be taken to protect women from certain health problems of risky sexual behavior.